Lysophosphatidylcholine Drives Neuroblast Cell Fate - Paoletti, Luciana Elisa (2015)
Neuronal differentiation plays a key role during embryogenesis. However, based on the capacity of neuronal stem cells to either generate or regenerate neurons and because differentiation stops aberrant neuroblasts proliferation, neuronal differentiation is crucial during neuropathological conditions. Although phosphatidylcholine (PtdCho) has been proposed as an important molecule for neurite growth and neuronal regeneration, the identity of the molecular target has remained elusive. This study originally describes that lysophosphatidylcholine (LPtdCho), either exogenously supplied or generated by the imbalance of PtdCho metabolism through the enzymatic action of cytosolic phospholipase A2, acts as a neurotrophic-like factor. We demonstrated that LPtdCho induces neuronal differentiation by activation of the small G protein Ras followed by the Raf/MEK/ERK signaling pathway. Accordingly, LPtdCho redirects neuroblasts gene expression leading to the generation of functional mature neurons expressing βIII-tubulin and having increased acetylcholinesterase activity and membrane biosynthesis required for neuritogenesis. These findings provide mechanistic details of the role of cytidine-5-diphosphocholine (CDP-choline) and PtdCho as neuroprotectors. Furthermore, as LPtdCho recapitulates the effect of the therapeutic agent retinoic acid, these results open new avenues for drug discovery for the treatment of neuropathological conditions.